The Politics of Chinese Investment in Africa under Belt and Road Initiative (BRI) Project - Dianjaya, Andika Raka (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
BRI project that will be held by China to connect countries in Europe, Asia, Middle East and Africa through Maritime Silk Road and Land Silk Road. This project will accelerate economy between countries who joined with this project. Africa as the potential partner have abundant resources energy that China require to maintain their position as the largest industrial producer in the world. China offering investment total of 60 billion to Africa and pledge to assist them to build infrastructure, technology, agriculture and any project that Africa need to develop their countries so they can compete in this globalization revolution industrial era. On this paper, we will analyse China position with their BRI project in Africa using Political Economy Approach by Weingast & Wittman and why China willingly to give investment total of 60 billion to Africa which is some Africa countries maybe can’t pay back their loans. Is this will become risk investment for China itself in the future?